The localization of ischemic stroke region in CT-images using a-priori information - Krylovas, Aleksandras; Štikonienė, Olga; Čiegis, Raimondas; Meilūnas, Mečislavas (Lietuvos matematikos rinkinys, 2004)
An algorithm for ischemic stroke region detection is proposed. It is based on analysis of differences between CT image of ischemic stroke patient and control image. An application of this method for region contour determination is also discussed.